Impact of Teachers’ Burnout on Their Motivation and Job Performance at the Secondary School Level - Dr. Atif Saeed Qureshi,; Dr. Fhaeem Khan, (Al-Amīr Research Journal for Islamic Studies, 2025)
The present study aimed to investigate the teachers burnout on their motivation and job performance. The study was conducted under positivism research philosophy. Correlational research design was used. The study was conducted at secondary school level of district Dera Ismile Khan (DIK). A sample of 280 secondary school teachers was selected by applying Yamane’s formula out of 935 secondary school teacher working in the district. For data collection, researcher used structuted questionnaire which was validated by Content Validity Ratio (CVR) and reliability score was estimated 0.779 By applying Cronbach’s alpha. Pearson product moment correlation and linear regression was used to check the relationship and causual effect between teacher burnout and motivation and job performance respectively. The result of the study indicates that teachers high level of burnout significantly decrease the teacher motivation and negatively correlated with job performance. In other words, teachers burn out has negative Predator of motivation and job performance. The study recommended that head of the schools may implement a support system in which may different services may be provided such as counselling, continuing professional development and workload reduction services to enhance the teachers motivation an job performance. Keywords: Teacher Burnout, Teacher Motivation, Job Performance, Secondary School Teachers